Troponin elevation predicts critical care needs and in-hospital mortality after thrombolysis in white but not black stroke patients - Faigle, Roland (J Crit Care, 2015)
INTRODUCTION: Stroke patients undergoing intravenous thrombolysis (IVT) are at increased risk for critical care interventions and mortality. Cardiac troponin elevation is common in stroke patients; however, its prognostic significance is unclear. The present study evaluates troponin elevation as a predictor of critical care needs and mortality in post-IVT patients, and describes racial differences in its predictive accuracy. METHODS: Logistic regression and receiver operating characteristics (ROC) analysis were used to determine racial differences in the predictive accuracy of troponin elevation for critical care needs and mortality in post-IVT patients. RESULTS: Troponin elevation predicted critical care needs in white (OR 29.40, 95% CI 4.86–177.81) but not black patients (OR 0.50, 95% CI 0.14–1.78; p-value for interaction <0.001). Adding troponin elevation to a prediction model for critical care needs in whites improved the area under the curve (AUC) from 0.670 to 0.844 (p=0.006); however, addition of troponin elevation did not improve the model in blacks (AUC 0.843 vs. 0.851, p=0.54). Troponin elevation was associated with in-hospital mortality in whites (OR 21.94, 95% CI 3.51–137.11) but not blacks (OR 1.10, 95% CI 0.19–6.32; p-value for interaction 0.022). CONCLUSION: Troponin is a useful predictor of poor outcome in white but not black post-IVT stroke patients.